2015
DOI: 10.1016/j.nantod.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicines for endothelial disorders

Abstract: The endothelium lines the internal surfaces of blood and lymphatic vessels and has a critical role in maintaining homeostasis. Endothelial dysfunction is involved in the pathology of many diseases and conditions, including disorders such as diabetes, cardiovascular diseases, and cancer. Given this common etiology in a range of diseases, medicines targeting an impaired endothelium can strengthen the arsenal of therapeutics. Nanomedicine – the application of nanotechnology to healthcare – presents novel opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 223 publications
0
39
0
Order By: Relevance
“…Additionally, the reports of more and more pre-clinical systems tailored for drug-delivery applications of nanocarriers emphasize the need for other nanomedical agents than just tumors 388 in the future, e.g. for cancer immunotherapy 389 or the treatment of endothelial disorders 390 and pulmonary diseases. 391…”
Section: Conclusion For Colloidal Capsules For Biological Applicationsmentioning
confidence: 99%
“…Additionally, the reports of more and more pre-clinical systems tailored for drug-delivery applications of nanocarriers emphasize the need for other nanomedical agents than just tumors 388 in the future, e.g. for cancer immunotherapy 389 or the treatment of endothelial disorders 390 and pulmonary diseases. 391…”
Section: Conclusion For Colloidal Capsules For Biological Applicationsmentioning
confidence: 99%
“…In comparison to traditional formulations, nanoparticle-based nanomedicines offer many distinctive characteristics such as: 1) improved bioavailability of poorly water-soluble drugs; 2) extended blood half-life through better protection before reaching the targets; 3) controlled drug release; 4) co-delivery of multiple types of therapeutic drugs and/or diagnostic agents (for instance, contrast/imaging agents) for combination therapy, real-time readout of therapeutic outcomes, or theranostics; and 5) targeted drug delivery to improve drug efficacy and reduce systemic side effects [32, 35]. These advantages have already been realized in those nanomedicines available on market or in clinic trials [34, 36, 59, 60].…”
Section: Nanomedicines and Approaches For Homing To Macrophagesmentioning
confidence: 99%
“…Among these, nanomedicine as an emerging field that utilizes nanotechnology concepts for advanced therapy and diagnostics has attracted major interest. It has been reported that the targeting of the plaques occurs via both the vasa vasorum and the main lumen at the lesioned sites [8,9]. Vasa vasorum is a network of small microvessels or capillaries entering the plaques from the opposite site.…”
Section: Introductionmentioning
confidence: 99%